Genre literacy transfer from the business to the social entrepreneurial pitch: A proposal for macrostructure and rhetorical strategies - Díez Prados, Mercedes (Círculo de Lingüística Aplicada a la Comunicación, 2026)
The generic characteristics of the entrepreneurial pitch (i.e., a short persuasive oral presentation to garner funding from investors) have been the focus of considerable interest in business communication studies for some decades now. Its condensed persuasive nature makes this genre a prototype for studying effective communication skills to move an audience. This paper shares insights gathered from a pedagogical experience in which university students in Modern Languages and Translation were trained to recognize the macrostructure and rhetorical strategies of business pitches, based on empirical research by Daly and Davy (2016), and transfer those skills to their own social entrepreneurial pitches. The analysis of the 31 pitches gathered revealed a new macrostructure, coined as the Problem-Solution-Evaluation-Request Pattern (i.e., a fusion between Hoey’s 1994 pattern and Searle’s 1969 Speech Act Theory), and the deployment of rhetorical strategies not included in the business model, mainly to appeal to positive and negative emotions. The results highlight the importance of genre literacy (Pérez-Llantada, 2021), and the new pattern and strategies may be of application to real-life social entrepreneurial pitching.